Improving health education: an investigation on VOC in UTHM libraries - Sulong, Muhammad Suhaimi (2008)
Indoor air quality (IAQ) has been a concern in the library since 1990s, when several employees working in the building reported occasional discomforts that may have been attributable to poor air quality. In the education world, library has been an important venue for students for various reasons no other than to enhance knowledge for the importance of their education. The purpose of this study is to measure the volatile organic compounds (VOC) in two libraries located at Universiti Tun Hussein Onn Malaysia (UTHM). Benzene, phenol, furfural, isobutene and toluene were five VOC gasses measured using the Photo Ionization Detector (PID) for eight working hours in two months. The results indicate that benzene and furfural gasses occurred as the highest VOC gasses detected in both libraries. The causes were due to the appearance of several equipments and tools frequently used in libraries such as papers, copying machines, carpets and book shelves. Moreover, the concentration of gasses detected was above the standard limit as accordance to the Environmental Protection Energy (EPA) and Occupational Safety and Health Act (OSHA). As a whole, several actions should be taken due to prevent unsafe environment in libraries as the existence of libraries play important role in education.